Strategi Marketing Public Relations PT.Global Dispo Medika Dalam Mengedukasi Produk Alat-Alat Kesehatan Kepada Pelanggan - Tatik Purwaningsih; Arnold Surya Nugroho (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
The medical device business in Indonesia is showing rapid progress, as evidenced by the increasing number of products from international brands and new companies engaged in medical devices entering Indonesia. Based on data from the Indonesian Ministry of Health, Directorate General of Pharmaceutical and Medical Devices Development, there are 359 medical device companies in Indonesia.The purpose of this study was to determine the Marketing Public Relations Strategy implemented in educating customers about medical device products.The theory used in this study is the theory of Scoot, M, Cutlip, Center, Allen H, and Broom which formulates specific Marketing Public Relations. The research method used is descriptive through a qualitative case study approach. The results showed that the Marketing Public Relations program carried out by PT. Global Dispo Medika included: exhibition, print and publication, all of the Marketing Public Relations activities described above had been carried out in accordance with the program that had been prepared so that the implementation went well and achieved target market.